Are they paying attention, or are they shoe-shopping? Evidence from online learning (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In response to the coronavirus pandemic, schools across the nation made an abrupt transition to teaching online as states instituted stay-at-home measures. This mixed methods study examines the attentiveness of adult learners in an online Doctorate of Education program. Three main findings emerged: 1) online courses where the students and instructor all are logged on to Zoom synchronously had higher average attentiveness compared to hybrid format courses where some students are physically in the classroom and some are on zoom; 2) average attentiveness was higher during the synchronous portion of classes with an asynchronous portion compared to fully synchronous online classes; and 3) average attentiveness was lower for class segments of over 30 minutes than class segments under 30 minutes.